Status and Direction of Atom Probe Analysis of Frozen Liquids. (August 2022) - Stender, Patrick; Gault, Baptiste; Schwarz, Tim M.; Woods, Eric V.; Kim, Se-Ho; Ott, Jonas; Stephenson, Leigh T.; Schmitz, Guido; Freysoldt, Christoph; Kästner, Johannes; El-Zoka, Ayman A.
Abstract: Abstract : Imaging of liquids and cryogenic biological materials by electron microscopy has been recently enabled by innovative approaches for specimen preparation and the fast development of optimized instruments for cryo-enabled electron microscopy (cryo-EM). Yet, cryo-EM typically lacks advanced analytical capabilities, in particular for light elements. With the development of protocols for frozen wet specimen preparation, atom probe tomography (APT) could advantageously complement insights gained by cryo-EM. Here, we report on different approaches that have been recently proposed to enable the analysis of relatively large volumes of frozen liquids from either a flat substrate or the fractured surface of a wire. Both allowed for analyzing water ice layers which are several micrometers thick consisting of pure water, pure heavy water, and aqueous solutions. We discuss the merits of both approaches and prospects for further developments in this area. Preliminary results raise numerous questions, in part concerning the physics underpinning field evaporation. We discuss these aspects and lay out some of the challenges regarding the APT analysis of frozen liquids.